Comparing discourse functions and syntactic complexity between face to face communication and computer mediated communication / Faizah Mohamad, Shamshad Begham Othman and Suhaila Sulong - Mohamad, Faizah; Othman, Shamshad Begham; Sulong, Suhaila (Institute of Research, Development and Commercialization (IRDC), 2007)
One of the features in today's computer assisted language learning is computer-mediated communication (CMC) and various studies on the benefits of CMC in language teaching and learning are widely conducted in language classrooms. The present study examines the discourse functions and syntactic complexity in the output of English as a second language learners (ESL) via two modes of discussion: face-to-face (F2F) and computermediated communication (CMC). 16 participants of the study involved in two face-to face discussions (first and fourth discussions) and two CMC discussions (second and third discussions) at a three-week interval. The discourse functions of these four discussions are measured by 14 categories identified by previous second language acquisition interactionist research. Meanwhile, the syntactic complexity of these four discussions is measured by eight categories identified by previous second language acquisition interactionist research. This study is also meant to investigate if CMC has any impact of the second language acquisition. The findings showed that the discourse functions have increased in many categories of CMC. It was also found that discourse functions decreased tremendously when the participants reverted from CMC to F2F discussions. With relation to syntactic complexity, it has increased in many categories of CMC discussions. Therefore, this study concluded that CMC has encouraged communicative fluency and language complexity among ESL learners and after conducting the CMC discussions, the learners seemed to use and acquire language better in their face-to-face discussions.